INCREASE THE COMPLETENESS OF THE NURSING DOCUMENTATION THROUGH THE IMPLEMENTATION OF THE NURSING INITIAL ASSESSMENT FORMS - Mariza Elvira (Stikes Syedza Saintika Padang, 2019)
Nurse had limited time to perform nursing documentation due to dense work load and limited number of nurse as well as the narrative format of documentation. Therefore, nursing assessment documentation was frequently incomplete. The study aim was to determine the effect of initial nursing assessment formaton the completeness of nursing assessment documentation in the internal ward of Padang Panjang District Hospital in year 2016. The study design was action research. Bivariate analysis was done by Wilcoxon’s test and multivariate analysis was done by Friedman’s test. Result showed that the implementation of nursing initial assessment checklist format increase the completeness of the nursing initial assessment documentation (p = <0.05). Nursing initial assessment checklist format could be applied to improve the completeness of nursing assessment documentation. It is recommended to hospital management to set the nursing initial assessment checklist format as the standard format usedand provide supervision and evaluation of this program. Keywords : checklist, innitial assessment, documentation